2019
DOI: 10.17582/journal.aavs/2019/7.11.1015.1020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Xylazine HCl and/or Ketamine HCl on the Tear Production in Clinically Healthy Dogs

Abstract: Objective: The effect of commonly used sedative and anesthetic drugs (xylazine and ketamine HCl) on tear production rate was evaluated in dogs using Schirmer tear test-I (STT I). Materials and Methods: Tear production using Schirmer tear strips were measured in healthy dogs before and after intramuscular injection of 1mg/kg of xylazine HCl (X; n = 4), 5 mg/kg of Ketamine HCl (K; n = 4), and combination of xylazine (1mg/kg) and ketamine (5 mg/ kg) (XK; n = 4). The tear production was recorded at times 0, 10, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…This finding corroborates other studies reporting that animals under deep anesthesia experience a reduced heart rate 15 min after ketamin-xylazine injection, irrespective of the use of levomepromazine as pre-anesthetic medication (Krause et al, 2016). In addition, the ketamine-xylazine combination is considered safe for maintaining the cardiorespiratory functions of dogs (Abdelhakiem et al, 2019). As observed in the present study, the xylazine-ketamine combination had a neutral effect on both HR and RR, causing non-significant changes (Abdelhakiem et al, 2019).…”
Section: Resultssupporting
confidence: 92%
“…This finding corroborates other studies reporting that animals under deep anesthesia experience a reduced heart rate 15 min after ketamin-xylazine injection, irrespective of the use of levomepromazine as pre-anesthetic medication (Krause et al, 2016). In addition, the ketamine-xylazine combination is considered safe for maintaining the cardiorespiratory functions of dogs (Abdelhakiem et al, 2019). As observed in the present study, the xylazine-ketamine combination had a neutral effect on both HR and RR, causing non-significant changes (Abdelhakiem et al, 2019).…”
Section: Resultssupporting
confidence: 92%
“…It was reported that α 2 -adrenoceptor agonists, including medetomidine, decrease tear flow in many species, such as dogs, cats, horses, and pigs [28][29][30][31][32][33][34][35][36][37]. The mechanism through which α 2 -adrenoceptor agonists decrease tear flow is not yet completely clarified, although local or systemic involvement of an α 2 -adrenoceptor was suggested in previous studies [28,31,32,34,36].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some α 2 -adrenoceptor agonists, including medetomidine, are administered not only alone, but also in combination with other drugs, such as opioids, benzodiazepine, phenothiazine, and ketamine [3,5,6,8,[21][22][23][24][25][26][27]. Although medetomidine and the other α 2 -adrenoceptor agonists used alone or in combination with other drugs have potent sedative or analgesic effects, they have been reported to significantly decrease tear flow in dogs [28][29][30][31][32], cats [33,34], horses [35,36], and pigs [37].…”
Section: Introductionmentioning
confidence: 99%
“…The 3 mm tips of threads were placed on the medial canthus for 15 s. The length of the moistened area from the edge was measured as the phenol red thread test (PRTT) value. Tear flow was measured approximately 1 min before (Pre) and 5,10,15,20,25,30,45, and 60 min after medetomidine administration.…”
Section: Measurementmentioning
confidence: 99%
“…Not only do α 2 -adrenoceptor agonists, including medetomidine, act as sedatives or analgesics to relieve animals from fear, anxiety, or pain, they also attenuate excessive neurohormonal reaction to the noxious stimulus, which contributes to maintaining homeostasis [5][6][7][8]. On the other hand, α 2 -adrenoceptor agonists such as medetomidine, dexmedetomidine, detomidine, xylazine, and clonidine have been reported to decrease tear flow in many animal species, including dogs, cats, horses, pigs, and rats [9][10][11][12][13][14][15][16][17][18]. Insufficient tear flow may cause structural or functional issues on the ocular surface, including the cornea, which induces pain or irritation [19][20][21].…”
Section: Introductionmentioning
confidence: 99%